Analiza porównawcza kryzysów bankowych Argentyny i Paragwaju - Ostalecka, Agnieszka (Comparative analysis of banking crises in Argentina and Paraguay, 2005)
The aim of this article is to conduct the comparative analysis of banking crises in two Latin American countries e.g. Argentina and Paraguay, which took place in the 1990s. This analysis is made in the following areas; reasons of banking crises outbreak, crisis development and authorities’ response to the banking crisis and consequences of banking crisis to both countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 110-118